Effects of long term resistance training on left ventricular morphology - Haykowsky, M. J.; Teo, K. K.; Quinney, A. H.; Humen, D. P.; Taylor, D. A. (Canadian Journal of Cardiology, 2000)
OBJECTIVES: To assess the effects of long term (mean +/- SD 10+/-5 years, range three to 25 years) resistance training on left ventricular (LV) dimensions and mass. METHODS AND RESULTS: The study participants were 21 elite male power-lifters (age 33.4+/-5.9 years) and 10 sedentary male control subjects (age 30.9+/-4.2 years). Two-dimensionally guided transthoracic M-mode echocardiograms were obtained at rest to quantify LV diastolic cavity dimension, posterior wall thickness, ventricular septal wall thickness and LV mass. Long term resistance training was not associated with an alteration in LV diastolic cavity dimension (resistance trained 54. 4+/-4.3 mm versus control 51.8+/-5.6 mm), ventricular septal wall thickness (resistance trained 9.7+/-1.0 mm versus control 10.1+/-0.7 mm), posterior wall thickness (resistance trained 9.6+/-1.5 mm versus control 9.3+/-1.4 mm) or LV mass (resistance trained 200. 3+/-32.5 g versus control 186.5+/-39.6 g). In addition, no resistance-trained athlete was found to have an LV mean wall thickness above clinical normal limits (12 mm or less). CONCLUSION: Contrary to common beliefs, long term resistance training as performed by elite male power-lifters does not alter LV morphology.